Pengaruh Kualitas Website Dan Promosi Melalui Sosial Media Instagram Terhadap Minat Beli Wisatawan Domestik Di The Westin Resort & Spa Ubud, Bali - Pande Putu, Dina Maharani; Pitanatri, Putu Diah Sastri; Clearesta Adinda (Journal of Hotel Management, 2024)
Purchase interest is a stage of tourist interest in a particular product or service that arisesfrom awareness and perception. Consumer buying interest will arise when consumers getinformation that can convince consumers about the products or services offered. Purchaseinterest is influenced by website quality and promotion. Promotion requires media indisseminating information. Promotional media that is easily accessible and can be tailored tothe needs of tourists is social media. The social media used is Instagram. This type of researchis quantitative, with the population being domestic tourists who have visited the website andInstagram of The Westin Resort & Spa Ubud, Bali in 2023. The data analysis techniques usedin this study are Multiple Linear Regression, t test, f test and Coefficient of Determination.